Goal-Oriented Error Estimation and Mesh Adaptation for Tracer Transport Modelling. (April 2022) - Wallwork, Joseph G.; Barral, Nicolas; Ham, David A.; Piggott, Matthew D.
Abstract: This paper applies metric-based mesh adaptation methods to advection-dominated tracer transport modelling problems in two and three dimensions, using the finite element package Firedrake . In particular, the mesh adaptation methods considered are built upon goal-oriented estimates for the error incurred in evaluating a diagnostic quantity of interest (QoI) . In the motivating example of modelling to support desalination plant outfall design, such a QoI could be the salinity at the plant inlet, which could be negatively impacted by the transport of brine from the plant's outfall. Four approaches are considered, one of which yields isotropic meshes. The focus on advection-dominated problems means that flows are often anisotropic; thus, three anisotropic approaches are also considered. Meshes resulting from each of the four approaches yield solutions to the tracer transport problem which give better approximations to QoI values than uniform meshing, for a given mesh size. The methodology is validated using an existing 2D tracer transport test case with a known analytical solution. Goal-oriented meshes for an idealised time-dependent desalination outfall scenario are also presented. Highlights: Derivation of a goal-oriented error estimate for tracer transport modelling. Implementation and comparison of four goal-oriented mesh adaptation approaches. Validation against an established test case with an analytical solution. Application of goal-oriented adaptation to an idealised desalination outfall problem.